The Believing Game or Methodological Believing - Peter Elbow (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
Three arguments why we need the believing game: to help us find flaws in our thinking, to help us choose among competing claims, and to achieve goals that the doubting game neglects.